2023
DOI: 10.1101/2023.10.13.23296599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of BRCA1 exon 11 genetic variations in breast cancer among Libyan women

Halla Elshwekh,
Inas Alhudiri,
Hamza Musbah Abdul Jalil
et al.

Abstract: Introduction The majority of hereditary breast and ovarian cancers are associated with mutations in two genes, breast cancer type 1 and 2 susceptibility genes (BRCA1 and BRCA2). Here, we describe for the first time analysis of BRCA1 exon 11 in 48 Libyan breast cancer patients with a family history of cancer. Methods All patients had a family history of cancer and were included in the study only if they have a family history of breast or ovarian cancer, male breast cancer, or triple negative tumors. PCR was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Sequencing of the BRCA1 gene within a cohort of patients with a family history of cancer revealed the presence of three novel variants (Table 1) previously unreported in studies conducted in Arab countries [16].…”
Section: Identification Of Novel Brca1 Exon 11 Variants and In Silico...mentioning
confidence: 85%
See 2 more Smart Citations
“…Sequencing of the BRCA1 gene within a cohort of patients with a family history of cancer revealed the presence of three novel variants (Table 1) previously unreported in studies conducted in Arab countries [16].…”
Section: Identification Of Novel Brca1 Exon 11 Variants and In Silico...mentioning
confidence: 85%
“…The three novel VUS characterized in this study (Table 1) were identified during a genetic screening carried out in the Oncology Departments of the main public hospitals in Tripoli (Tripoli Central Hospital and Tripoli Medical Center). Complete clinical information on the analyzed patients is reported in a MedRxiv preprint [16]. The table shows the type of variation (missense/synonymous); the resulting amino acid change; and the GenBank identification number as described in a recent preprint [16].…”
Section: Novel Variants Of Uncertain Significancementioning
confidence: 99%
See 1 more Smart Citation